Forced Migrants: Strategies of Controlling the Life Difficulties - Евгения Сергеевна Балабанова (Journal of Economic Sociology, 2010)
The author investigates the forced migration from CIS countries under the conception of controlling the life difficulties. Controlling behavior is described as the process of running the personal, social and material resources. This approach let us reveal the dynamics of individual behavior under the difficult life circumstances, focusing on personal resources. The result of the behavior in the difficult life situation is the movement along the scale of “accumulating advantages – intensification of deprivation”. The author analyzes the factors that influence the vector of this movement. Data source is the poll and two series of interviews with migrants in Ekaterinburg, Krasnodar, Moscow and Nijni Novgorod.